Nipah virus: phylogeny and replication - Chang, L.Y.; AbuBakar, Sazaly (2009)
Phylogenetic analysis of Nipah virus isolates from Malaysia, Bangladesh and Cambodia suggested the presence of at least two different clusters of NiV strains. Based on the major glycoprotein ( G) gene, the Nipah virus-Tambun isolate clustered with Nipah virus isolates from Cambodia and Bangladesh, whereas the remaining isolates from Malaysia clustered in a separate cluster. Sequence heterogeneity among the Nipah virus isolates from Malaysia was noted but the overall genomic sequence divergence value was small, suggesting a possible recent introduction of the virus. Nipah virus replicated well in porcine stable kidney cells and human lung fibroblast cells. Human monocytes, on the other hand were infected with Nipah virus but the cells did not support productive infection. Similarly, infection of human neuronal cells did not result in release of high infectious virus yield. The monocytes can serve to disseminate Nipah virus from site of infection including across the blood-brain barrier. And in the brain, Nipah virus is probably spread through cell-to-cell spread mechanism.